Impact of Hydrogen Peroxide Concentration on Diclofenac Degradation by UV/H2O2: Kinetic Modeling for Water Treatment Applications - Natalia Villota; Unai Duoandicoechea; Begoña Echevarria; Ana María de Luis (Separations)
This study researches the impact of diclofenac (DCF) oxidation via UV/H2O2 on water quality, focusing on aromaticity and color changes. The process effectively degrades DCF and its intermediates through hydroxyl radical attack on the aromatic structure, leading to the formation of oxidized by-products. Initially, chromophoric compounds such as quinones and conjugated intermediates cause a yellow coloration, which diminishes as mineralization progresses. Turbidity remains below 1 NTU, aligning with European water quality standards. Aromaticity initially increases due to the stable intermediates (e.g., catechols and hydroquinones) but decreases as advanced oxidation cleaves aromatic rings. Kinetic modeling shows that DCF degradation follows first-order kinetics, while aromatic intermediates degrade via fractional-order kinetics (~0.3), indicating a non-linear relationship with concentration. The formation of chromophore compounds follows first-order kinetics, whereas their degradation transitions to zero-order kinetics when hydroxyl radicals are abundant. The study highlights the environmental relevance of these transformations, as aromatic intermediates like anilines and phenols, which contribute to water toxicity, are ultimately converted into less hazardous compounds (e.g., carboxylic acids and inorganic ions). Experimental validation confirms that degradation kinetics depend on hydrogen peroxide concentration, underscoring the potential of UV/H2O2 for water purification and pollutant removal.